Pelatihan Microsoft Office Excel Sebagai Upaya Peningkatan Kompetensi Siswa SMKN 1 Praya Tengah Dalam Mengolah Data - Heru Karuniawan; Sofiansyah Fadli; Baiq Rianis (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The right information can be obtained with good data management. For accurate business decision making, organizations need this information. It is very important for vocational school students to understand data processing so that they can improve their performance in the industrial sector. As a strategy for preparing vocational school students for the world of work, training in using Microsoft Office Excel 2013 for data processing is very useful. At SMKN 1 Praya Tengah, students are involved as partners in this training. The program begins with a pre-test to measure students' initial abilities, followed by scheduling training with partners, creating material based on pre-test results, implementing training, and closing with an evaluation of learning outcomes. The results show students' ability to use various formulas in Microsoft Office Excel 2013 to process data. This contributes to improving graduate skills and the quality of education at SMKN 1 Praya Tengah.